Evaluation of grooving method to postpone debonding of FRP laminates in WPC-FRP beams - Arefi, Shahin Lale; Naghipour, Morteza; Turskis, Zenonas; Nematzadeh, Mehdi (Journal of Civil Engineering and Management, 2014)
The use of lightweight construction material with high corrosion resistance and low cost plays an important role in the design and construction of marine structures such as waterfronts. One of the most common methods for strengthening the structures is composite fibre reinforced plastic (FRP) sheet that is used for member retrofitting including wood plastic composite (WPC). The WPC material is produced from wood and compressed resin, which has good mechanical properties as well as economic benefits. The main problem of WPC reinforced with FRP sheets is the debonding of the sheet from WPC surface, which leads to premature and non-economic failure in members. One of the existing methods to solve this problem is surface preparation. However, surface preparation of wood plastic composite has some additional problems, such as operational cost, environmental pollution, etc. Therefore, to avoid debonding, another method has been used, known as the grooving method at the lower parts of beams. The laboratory used 50 I-shaped specimens with the same geometrical and mechanical properties. Initially, some slots such as longitudinal, transverse and diagonal grooves were created on the surface of specimens and filled by an epoxy. All beams were armed using one or two layers of GFRP sheets embedded at the lower part and were tested under four-point flexural loading. Grooves of different shapes, various widths and depths as well as the number of reinforcement layers were determined for considering their effect on the beam's behaviour. The results expressed that the debonding of FRP sheets can be delayed by selecting the longitudinal grooves with certain width and depth, which also leads to resistance improvement.